Assessment of Preoperative Anxiety Utilizing Amsterdam Preoperative Anxiety and Information Scale in Patients Undergoing Intracranial Tumor Surgery: An Exploratory Study - Chandra, Vikram; Goel, Nishant; Kumari, Ranjeeta; Agrawal, Sanjay (Journal of Neuroanaesthesiology and Critical Care, 2024)
Background Preoperative anxiety in neurosurgical patients is high due to life-threatening illness and uncertainty of the surgical outcome. This study assessed preoperative anxiety and its influencing factors in patients undergoing intracranial tumor surgeries utilizing the Amsterdam Preoperative Anxiety and Information Scale (APAIS).Methods One-hundred twenty patients, 18 to 65 years of age, of either sex, American Society of Anesthesiologists (ASA) grades I/II posted for elective craniotomy and tumor excision, were selected for the study. Various components of the APAIS were explained, and the level of anxiety and need for information were noted. The level of anxiety and depression by HADS (Hospital Anxiety and Depression Scale) score was also evaluated.Results The mean age was 38.00 ± 12.15 years. About 57.5% of the patients were male. Eighteen (15%) patients had an educational qualification of class 10, 60(50%) of 10 + 2, 36 (30%) were graduates, and 6 (5%) had a postgraduate qualification.The mean APAIS for total anxiety was 11.10 ± 1.79; the score for need for information was 6.28 ± 1.61. Mean total anxiety scores were higher in female patients (11.96 vs. 10.46, p < 0.001). Higher anxiety was observed in ASA status I patients (11.33 vs. 10.539 ASA I vs. II, p = 0.020). Significantly higher anxiety was observed in patients educated till class 10 (p = 0.012). A significantly higher need for information was observed in postgraduates (p = 0.012). Eighty (66.7%) patients had clinical anxiety, and 35 (29.2%) had clinical depression on the HADS score.Conclusion Neurosurgical patients have higher anxiety due to intracranial pathology, site of surgery, and unpredictability of outcome. Demographic and clinical variables do affect anxiety levels.
Keywords: anxiety; intracranial tumor; assessment; Amsterdam Preoperative Anxiety and Information Scale; HADS